Effect of protein level and slaughter age on carcass traits and meat quality of Bruna Alpine steers - De Marzo, Davide; Laudadio, Vito; Tufarelli, Vincenzo (Progress in Nutrition, 2022)
This study aimed to evaluate the effects of dietary protein level on the growth performance, carcass traits and meat quality of Bruna Alpina steers slaughtered at different ages. Animals were weighing approximately 260 kg and were divided equally into two treatment groups. Group A received a Crude Protein deficient diet (8.50 %) wile group B was given adequate crude protein throughout the study (12.20 % crude protein on a dry matter basis). Four cattle from each group were slaughtered at approximately 30 days intervals. Carcasses were yield graded and chilling took place at 3° C and were aged for 21 days at 4 °C. Proximate analysis of Longissimus muscle were determined and separable components of 11th rib were separated. Cattle in group B which had been fed adequate protein were heavier at slaughter than cattle in group A which was fed the protein deficient diet (486.1 versus 442.4 Kg; p < .05) and ADG (1.02 versus 0.63 kg/d; p < .01). As for proximate composition of LD muscle groups 190 and 150 days were characterized by the lowest protein (p<.05), instead LD from group 190 days showed the highest lipid content (6.98%). We concluded that increasing the amount of dietary protein as used in this study tended to improve some carcass quality.